2013
DOI: 10.37190/epe130109
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of total petroleum hydrocarbons and polycyclic aromatic hy-drocarbons in Musa Bay sediments (northwest of the Persian Gulf)

Abstract: Sediment samples were collected from the coastal area of the Petrochemical Special Economic Zone of Musa Bay. The samples were analyzed to determine the degree of hydrocarbon contamination and identify the sources of PAHs which were evaluated by employing the ratios of specific PAHs compounds and principal component analysis (PCA). The levels of TPH concentration in the studied area were relatively moderate compared to the world-wide chronically oil-contaminated locations. The concentration of total PAHs was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…Our study, therefore indicate that CRP-Cardón is a heavily-polluted area which exceeds by an order of magnitude (i.e., 2.500 ppm) the concentration of TPH reported in other oil refineries overseas (e.g. the Persian Gulf: 200 ppm, Tehrani et al, 2013 ). In general, our results indicated that levels of pollution of particular contaminants such as Hg, Pb, Cd and TPH in sites close to the oil refineries that have been operating in the area for decades are above local and international recommended standards.…”
Section: Discussioncontrasting
confidence: 49%
“…Our study, therefore indicate that CRP-Cardón is a heavily-polluted area which exceeds by an order of magnitude (i.e., 2.500 ppm) the concentration of TPH reported in other oil refineries overseas (e.g. the Persian Gulf: 200 ppm, Tehrani et al, 2013 ). In general, our results indicated that levels of pollution of particular contaminants such as Hg, Pb, Cd and TPH in sites close to the oil refineries that have been operating in the area for decades are above local and international recommended standards.…”
Section: Discussioncontrasting
confidence: 49%
“…Generally, the levels of sediment TPH in the studied area were found significantly lower than those obtainable in many other coastal environments like Ceuta harbour in North Africa [ 93 ]; Musa Bay [ 94 ] and Barnegat-Bay-Little Egg Harbor Estuary, USA [ 95 ]. However, water from few other locations around the world revealed petroleum hydrocarbons concentrations that were similar to those reported in this study.…”
Section: Resultsmentioning
confidence: 65%
“…There is a considerable effort to determine the titanium and titanium compounds in industrial applications and their corresponding hazardous effects to humans and the environment 2 3 4 5 . Several methods have been reported, such as gravimetric filter weight (G/FW) 6 and inductively coupled argon plasma-atomic emission spectroscopy (ICP-AES) 7 8 9 .…”
mentioning
confidence: 99%